Imaging biobanks: operational limits, medical-legal and ethical reflections - Capasso, Emanuele; Casella, Claudia; Marisei, Mariagrazia; Tortora, Mario; Briganti, Francesco; Di Lorenzo, Pierpaolo (Frontiers in Digital Health, 2024)
The extraordinary growth of health technologies has determined an increasing interest in biobanks that represent a unique wealth for research, experimentation, and validation of new therapies. “Human” biobanks are repositories of various types of human biological samples. Through years the paradigm has shifted from spontaneous collections of biological material all over the world to institutional, organized, and well-structured forms. Imaging biobanks represent a novel field and are defined by European Society of Radiology as: “organized databases of medical images, and associated imaging biomarkers shared among multiple researchers, linked to other biorepositories”. Modern radiology and nuclear medicine can provide multiple imaging biomarkers, that express the phenotype related to certain diseases, especially in oncology. Imaging biobanks, not a mere catalogue of bioimages associated to clinical data, involve advanced computer technologies to implement the emergent field of radiomics and radiogenomics. Since Europe hosts most of the biobanks, juridical and ethical framework, with a specific referral to Italy, is analyzed. Linking imaging biobanks to traditional ones appears to be a crucial step that needs to be driven by medical imaging community under clear juridical and ethical guidelines.